2013
DOI: 10.1074/jbc.m113.488528
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Serotype 11D Has a Bispecific Glycosyltransferase and Expresses Two Different Capsular Polysaccharide Repeating Units

Abstract: Background: Streptococcus pneumoniae serotype 11D capsular polysaccharide (CPS) structure is unknown. Results: Serotype 11D PS contains two different repeating units; one has ␣GlcNAc, and the other contains ␣Glc. Conclusion: The 11D CPS is due to the bispecific glycosyltransferase WcrL. Based on codon 112, WcrL can transfer ␣Glc, ␣GlcNAc, or both. Significance: Minimal genetic changes can make bacteria produce different polysaccharides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 36 publications
2
39
0
Order By: Relevance
“…In contrast, wcjE sequences of the 11Av strains 3102-06, MZN265, and MNZ2293-C differ from the wcjE sequences of their 11A counterparts by only one nucleotide substitution. Similarly, sequences of the serotype 11D and 11A-1 cps loci differ by only a single nucleotide substitution (8) and, as discussed above, nucleotide polymorphisms resulting in notable antigenic changes are reported for serogroups 6 and 9 (6,25). In light of this evidence, genetic profiling of cps loci cannot unambiguously predict capsule identity, and the ability to serologically characterize pneumococcal strains remains crucial.…”
Section: Figmentioning
confidence: 95%
See 2 more Smart Citations
“…In contrast, wcjE sequences of the 11Av strains 3102-06, MZN265, and MNZ2293-C differ from the wcjE sequences of their 11A counterparts by only one nucleotide substitution. Similarly, sequences of the serotype 11D and 11A-1 cps loci differ by only a single nucleotide substitution (8) and, as discussed above, nucleotide polymorphisms resulting in notable antigenic changes are reported for serogroups 6 and 9 (6,25). In light of this evidence, genetic profiling of cps loci cannot unambiguously predict capsule identity, and the ability to serologically characterize pneumococcal strains remains crucial.…”
Section: Figmentioning
confidence: 95%
“…Successful recombination was verified by sequencing of the wcjE locus in all recombinant strains. The capsule-null variant AMB03 was created by recombinatorial replacement of the JC03 cps region spanning from wchA to wcrL with a Janus cassette containing the respective flanking regions, as described previously (8). Loss of capsule expression was verified by colony morphology and the Quellung reaction using factor serum 11c, which contains antibodies that bind to serotype 11A, 11C, 11D, and 11E capsule PSs (3).…”
Section: Pneumococcal Clinical Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown that different strains of the same serotype can have significant genetic differences in their cps loci. For instance, many serotype 11A strains isolated from the United States and Europe have large differences in their cps DNA sequences, resulting in misidentification of some 11A isolates as 11D in the past (19)(20)(21). Also, serotype 19A cps loci can be significantly different among different isolates (22).…”
Section: Discussionmentioning
confidence: 99%
“…Mild methanolysis is required for the detection of 3-deoxy-D-manno-oct-2-ulosonic acid (KDO), which is used by bacteria in the synthesis of lipopolysaccharides (65)(66)(67). GlcNAc also easily destroyed during hydrolysis therefore mild acid condition or methanolysis is needed (68)(69)(70)(71). On the contrary, liberation of all monosaccharides from polysaccharides is also not easily achieved, especially uronic acid-containing polysaccharides because glycosidic linkages between uronic acids and other monosaccharides are acid resistant during acid treatments.…”
Section: Acidic Hydrolysismentioning
confidence: 99%